2017
DOI: 10.1002/ajh.24880
|View full text |Cite
|
Sign up to set email alerts
|

World Health Organization‐defined eosinophilic disorders: 2017 update on diagnosis, risk stratification, and management

Abstract: Disease overview: The eosinophilias encompass a broad range of nonhematologic (secondary or reactive) and hematologic (primary, clonal) disorders with potential for end-organ damage.Diagnosis: Hypereosinophilia has generally been defined as a peripheral blood eosinophil count greater than 1500/mm 3 and may be associated with tissue damage. After exclusion of secondary causes of eosinophilia, diagnostic evaluation of primary eosinophilias relies on a combination of morphologic review of the blood and marrow, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
270
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(303 citation statements)
references
References 167 publications
4
270
0
6
Order By: Relevance
“…1,2 HES is characterized by peripheral eosinophilia and eosinophilic tissue/end-organ damage. 1,2 HES is characterized by peripheral eosinophilia and eosinophilic tissue/end-organ damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 HES is characterized by peripheral eosinophilia and eosinophilic tissue/end-organ damage. 1,2 HES is characterized by peripheral eosinophilia and eosinophilic tissue/end-organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 HES is characterized by peripheral eosinophilia and eosinophilic tissue/end-organ damage. 2 The clinical presentation of HES is extremely highly variable ranging from a relatively asymptomatic disease to endomyocardial fibrosis. 1 Regarding the latest consensus, several clinical subtypes/ categories have been identified that are different from the previous categories and definitions.…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils are terminally differentiated granulocytes that are produced in the bone marrow via a collection of transcription factors and cytokines including interleukin 5 (IL‐5), interleukin 3 (IL‐3), and granulocyte macrophage colony stimulating factor (GM‐CSF) . Maturation occurs in the bone marrow over a five‐day period, and mature cells are released into circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Normal eosinophil percentage is between 1%‐6% in the bone marrow and 3%‐5% in the peripheral blood, equating to an absolute peripheral eosinophil count (AEC) of 0.35‐0.5 × 10 9 /L . Eosinophilia is arbitrarily designated as mild (up to 1.5 × 10 9 /L), moderate (1.5‐5 × 10 9 /L), and severe (>5 × 10 9 /L) . Workup of eosinophilia to exclude a clonal process would be warranted in patients with persistent, unexplained eosinophilia.…”
Section: Introductionmentioning
confidence: 99%
“…An algorithm that may facilitate the identification of the underlying cause is recommended in the evaluation of patients with HE [5] (Fig. 1).…”
mentioning
confidence: 99%